2004
DOI: 10.1038/sj.onc.1207851
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic squamous cell carcinoma cells that overexpress c-Met exhibit enhanced angiogenesis factor expression, scattering and metastasis in response to hepatocyte growth factor

Abstract: We previously performed gene expression profiling in a multistep squamous cell carcinoma (SCC) progression model, and identified growth-regulated oncogene-1 (Gro-1/KC) as a factor that contributes to enhanced angiogenesis, tumorigenesis and metastasis. In the present study, we explored molecular pathways coactivated with Gro-1/ KC, and identified a transcript that encodes c-Met, the receptor for hepatocyte growth factor/scatter factor (HGF). Northern, Western blot, and immunohistochemical analyses confirm that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…Thus, the aberrant function of molecules controlling the synthesis and degradation of phosphatidylinositol 3,4,5-triphosphate, phosphatidylinositol 3 ¶-OH kinase, and PTEN may help explain the presence of activated Akt in the absence of persistent EGFR signaling. This, as well as the possibility that other overactive tyrosine kinase growth factor receptors, such as c-Met or HER2 (59,60), may result in the EGFR-independent stimulation of Akt in HNSCC, warrants further investigation. Of interest, a surprising observation in this TMA analysis was that the proportion of HNSCC cases that were positive for Akt Thr308 was smaller than that of Akt Ser473 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aberrant function of molecules controlling the synthesis and degradation of phosphatidylinositol 3,4,5-triphosphate, phosphatidylinositol 3 ¶-OH kinase, and PTEN may help explain the presence of activated Akt in the absence of persistent EGFR signaling. This, as well as the possibility that other overactive tyrosine kinase growth factor receptors, such as c-Met or HER2 (59,60), may result in the EGFR-independent stimulation of Akt in HNSCC, warrants further investigation. Of interest, a surprising observation in this TMA analysis was that the proportion of HNSCC cases that were positive for Akt Thr308 was smaller than that of Akt Ser473 .…”
Section: Discussionmentioning
confidence: 99%
“…HGF/c-MET receptor-induced activation of the mitogen-activated protein kinase kinase (MEK) and phosphatidylinositol 3-kinase (PI3K) signal pathways was previously shown to contribute to expression of IL-8 and VEGF by HNSCC and other cells (9,10). We also recently showed that enforced expression of HGF promoted expression of homologues Gro 1 and VEGF and angiogenesis, tumorigenesis, and metastasis of SCC overexpressing c-Met in a murine model (11). VEGF, IL-8, and Gro 1/Gro a (KC in mouse) have been shown to be key factors in mediating angiogenesis in SCC and other cancers (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 92%
“…Certain studies have demonstrated that HGF can enhance the generation of GRO-1 and VEGF in vitro (38) and another study indicated that serum levels of HGF in head and neck squamous cell carcinoma can regulate the expression of PDGF-A (39). There were correlations between two of either GRO-1, HGF and PDGF-AA in the present study, which suggests that they have a common role in angiogenesis (11,17,40), while no association was found between sE-selectin and GRO-1 and PDGF-AA.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%